Lactobacillus johnsonii‐FM1 modulates gut microbiota and secretes anticancer metabolite vanillic acid to inhibit colorectal tumorigenesis - Wei Lyu; Lu Chen; De‐Feng Li; Shu‐Ying Li; Qian Dai; Hong‐Li Zhou; Yan‐Yan Liu; Jian‐Yun Zhou; Xin‐Jun Liang; Ling Wang (iMetaOmics, 2025)
Abstract During colorectal cancer (CRC) progression, probiotics support gut microbial balance, enhance intestinal barrier integrity, and exert antioxidant and anti‐inflammatory effects. Such supplementation may slow tumor growth and serve as an adjunctive therapy for CRC. In this study, we evaluated the impact of Lactobacillus johnsonii‐FM1 in ApcMin/+ and azoxymethane/dextran sulfate sodium‐induced CRC mouse models. Our results demonstrate that L. johnsonii‐FM1 markedly reduces tumor number, size, and volume in both models. Shotgun metagenomic sequencing showed that L. johnsonii‐FM1 increases the abundance of potentially beneficial taxa while decreasing opportunistic pathogens, thereby preserving gut barrier function. Moreover, untargeted metabolomics paired with liquid chromatography‐tandem mass spectrometry identified vanillic acid (VCA) as a key bioactive metabolite produced by L. johnsonii‐FM1. In vitro, VCA inhibits CRC cell line proliferation, diminishes colony formation, induces cell‐cycle arrest, and promotes apoptosis. Mechanistically, VCA attenuates CRC progression by suppressing Wnt/β‐catenin signaling. Our findings suggest a promising probiotic‐based adjunctive strategy for CRC prevention and treatment.